Estudo dos fatores que influenciam o processo de luminescência de sistemas contendo íons európio trivalentes: da investigação à aplicação - Ferreira, Monica dos Santos (2019)
Chemistry of the lanthanides (Ln) continues to arouse great interest in the midst of the technological advance, given its vast area of applications. Among the Ln, the trivalent europium ion (Eu3+) is the most studied. In this context, theoretical studies have become increasingly common to analyze essential spectroscopic properties aimed at obtaining compounds with potential applications. The general objective of this dissertation is to explore phenomena involved in the process of luminescence of systems containing trivalent europium using theoretical tools. By means of correlations it was possible to analyze: i) triplet energy × quantum yield (q), ii) RL (triplet) × q, iii) Arad × q, and finally, Anrad × q. It was verified that when the energy of the triplet state takes values around 20,000 cm-1 we have good results for the quantum yield, while for values smaller than 17,000 cm-1 q tends to zero; high RL distances reduce q; Arad and Anrad interfere in opposite ways in the quantum efficiency, associating high rates of radiative emission and low non-radiative emission rates point an increase in the quantum yield. A strategy of design of highly efficient systems was also developed, using semi-empirical models developed for the determination of intensity parameters and non-radiative emission rate. An efficient systems design strategy was also developed through semiempirical models developed for the determination of intensity parameters and non-radiative emission rate, based on the matrix system [Eu(btfa)3(dmbpy)]. Such models enabled the theoretical design process of ligands that enhanced the antenna effect by modifying the ends of the benzoyl trifluoroacetate (btfa) ligand. The phenyl group was modified with the NHCH3 group in the ortho position and at the other end of the binder the CF2CF3 group was added. It was possible to design a system with theoretical quantum yield of 67%, when for the matrix system the value of q was 44%. In another study, the spectroscopic properties of four major new classes of highly luminescent Eu3+ homobimetallic complexes containing the naproxen non-steroidal anti-inflammatory drug (NSAID) were investigated experimentally and theoretically. Due to their solubility and high quantum efficiency values, such complexes are potential candidates for the construction of biosensors. These studies allowed a better understanding of the behavior of luminescent properties in the studied systems, as well as the importance of their relationship with the structural composition. Given the proposals adopted, the LUMPAC program proved to be a powerful tool, enabling the study of luminescent properties of systems containing the trivalent europium ion in different strands. This feature not only enabled the proposition of a theoretical design protocol for this type of systems, but also generated models that contributed to the development of better theoretical-experimental studies.